Strategies for the Suitability of Self-assembled Supramolecular Polymersomes in Drug Delivery and Diagnostics - Bharkatiya, Meenakshi; Sharma, Komal (Indian Journal of Pharmaceutical Education and Research, 2022)
Amphiphilic copolymers which can self-organize into distinct nano vesicles comprising of hydrophilic core and a hydrophobic bilayer membrane with innumerable morphologies have wide applications ranging from cell mimics to diagnostics. The flexibility to control the size, shape, morphology, functionality and surface properties makes polymersomes widely acceptable. The suitability of these systems for various biomedical applications exhilarated because of its robust responsiveness to both internal and external stimuli at the site of interest. The biodegradability with lesser toxicity adds up to its acceptability as an innate cargo molecule. A large share of research works published on the polymersomes in recent years showcase this vesicle as a future device of choice for targeted drug delivery and bio imaging. But the effectiveness of these systems meticulously relays on the precise engineering of physical, morphological and surface characteristics supported by thorough understanding on the various aspects of its designing. With an intention of accelerating multiple dimensions of polymersome research, this article focuses on recapitulating those controllable essential attributes of polymersomes. It also reveals how changes in these variables contribute to polymersomes becoming an important potential freight moiety for a variety of biomedical relevence.
Keywords: Polymersomes; PEG; Amphiphiles; Payload; Stimuli